Investigaciones sobre cascadas electromagnéticas - Orellana, Mariana Dominga (2013)
Results from the latest generations of telescopes have revealed a rich sky at high and very high energies with more than a thousand sources at GeV energies and more than a hundred sources at TeV energies. The sources are galactic and extra-galactic natural particle accelerators where emission processes operate efficiently at the gamma-ray domain. The development of pair-photon cascades within the source or along the line of sight may modify the originally emitted spectrum. This effect should be included in our interpretation of the observations in order to progress in the understanding of the physical origin of the emission.Through numerical simulations we follow the three-dimensional trajectories of such cascades. I here report on the status of our investigations, with focus on the propagation through the background photon fields.